Perancangan Interior Hershey’s Chocolate World di Surabaya - Elisa Novita; I Gusti Ngurah Ardana (Intra, 2016)
Chocolate is a food which is loved by many people, regardless of age. Currently, chocolate’s type, flavor, and shapes is different and have varied. Nevertheless, the selling system of chocolate in Surabaya is still very conventional. In order for the chocolate sales to grow and become a profitable business opportunity, it is necessary to design the interior of chocolate shop that provides a challenge to the public to learn how to produce chocolate as a part of shopping activity and simultaneously an alternative way to spend time with family. In order for these efforts to be realized, this design is done through the process of data collecting, using qualitative and analysis method. Based on the design concept, Sweet and Sparkling as Vegas, the interior of Hershey’s Chocolate World in Surabaya is facilitate with conventional shopping with factory tour facility to see the actual process of chocolate production. Some supporting facilities designed to entertain visitors are: Hershey’s Chocolate Tour, Hershey’s Make Your Own Chocolate Bar, Hershey’s Wrapper Happiness, Hershey’s Cooking Class, Hershey’s Café, and Hershey’s Store.